The Nosocomial Transmission of Carbapenem-Resistant Gram-Negative Bacteria in a Hospital in Baoding City, China - Shengnan Liao; Wei Su; Tianjiao Li; Zeyang Li; Zihan Pei; Jie Zhang; Wenjuan Yin (Microbiology Research)
Background: The global rise of multidrug-resistant Gram-negative bacteria, particularly non-fermenting species and carbapenemase-producing Enterobacteriaceae, poses a significant challenge to hospital infection control. Methods: In this study, a total of 89 Acinetobacter spp. isolates, 14 Pseudomonas aeruginosa, and 14 carbapenem-resistant Enterobacteriaceae isolates were collected from patients in a tertiary hospital. Whole-genome sequencing and antimicrobial susceptibility testing were conducted. Resistance mechanisms and evolutionary relationships were analyzed using phylogenetic analysis and genetic context mapping. Results: Among the non-fermenting isolates, A. baumannii exhibited high resistance to carbapenems, clustering into distinct clonal groups enriched with genes associated with biofilm formation and virulence genes. P. aeruginosa isolates harbored fewer resistance genes but carried notable mutations in the efflux pump systems and the oprD gene. In Enterobacteriaceae, four blaNDM alleles were identified within a conservative structural sequence, while blaKPC-2 was located in a non-Tn4401 structure flanked by IS481- and IS1182-like insertion sequences. Phylogenetic analysis revealed that blaNDM-positive E. coli strains were closely related to susceptible lineages, indicating horizontal gene transfer. Conversely, K. pneumoniae isolates harboring blaKPC-2 formed a tight clonal cluster, suggesting clonal expansion. Conclusions: The study reveals distinct transmission patterns between resistance genes: horizontal dissemination of blaNDM and clonal expansion of blaKPC-2 in K. pneumoniae. These findings emphasize the need for resistance-gene-specific genomic surveillance and infection control strategies to prevent further nosocomial dissemination.